Composition for preparing superabsorbent polymer and method for preparing superabsorbent polymer using same
By using a composition of water-soluble ethylenically unsaturated monomer and polymer dispersant in superabsorbent polymers, combined with heating and irradiation photopolymerization and surface crosslinking technology, the problem of clay particles is solved and clay is realized The uniform dispersion and long-term stability improve the absorption performance and color characteristics of superabsorbent polymers.
Patent Information
- Application Number
- CN202480002582.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-02-29
- Filing Date
- 2024-03-04
- Publication Date
- 2024-12-20
AI Technical Summary
In the existing superabsorbent polymers, clay particles are prone to aggregate in high ion concentration solutions, resulting in uneven dispersion, making it difficult to maintain stability during the preparation process, affecting performance.
Using a composition containing a water-soluble ethylenically unsaturated monomer and a polymer dispersant, polymerization reaction is carried out by heating and irradiation to form an aqueous gel polymer, and the base polymer is prepared by drying and crushing, and then crossing it on the surface. Surface crosslinking is performed in the presence of a coupling agent to form a surface crosslinking layer to improve the dispersion of the clay.
The uniform dispersion and long-term stability of clay particles are achieved, the absorption performance and color characteristics of superabsorbent polymers are improved, and the high quality of the product is ensured.
Smart Images

Figure CN119173542A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of Korean Patent Application No. 10-2023-0028618 filed on March 3, 2023, and Korean Patent Application No. 10-2024-0030239 filed on February 29, 2024, in the Korean Intellectual Property Office, the disclosures of which are incorporated herein by reference in their entirety. [Technical field]
[0003] The present invention relates to a clay dispersion having excellent clay dispersion stability, a composition for preparing a super absorbent polymer comprising the clay dispersion, and a method for preparing a super absorbent polymer using the clay dispersion. [Background Technology]
[0004] Superabsorbent polymers (SAP) are synthetic polymer materials that can absorb 500 to 1000 times their own weight in water. Since superabsorbent polymers began to be practically used in sanitary products, they are now widely used not only in sanitary products such as disposable diapers for children, sanitary materials for sanitary napkins, etc., but also in water-retaining soil products for gardening, water-stopping materials for civil engineering and construction, sheets for seedling cultivation, preservatives for the food distribution field, materials for potting, etc.
[0005] Attempts are being made to introduce additives to improve basic properties of superabsorbent polymers, such as centrifuge retention capacity (CRC) and absorbency under pressure (AUP), and clay is one of them. However, clay particles tend to aggregate with each other in a solution with a high ion concentration, making it difficult to ensure dispersion stability. Therefore, it is difficult to uniformly disperse clay in a monomer composition for manufacturing superabsorbent polymers, and therefore, aggregated clay is unevenly distributed in the manufactured superabsorbent polymer in the form of particles, making it difficult to obtain the effect of improving the properties of superabsorbent polymers.
[0006] Therefore, there is a need to develop a clay dispersion that can exhibit excellent dispersibility in a composition for preparing a super absorbent polymer and improve the physical properties of the super absorbent polymer. [Summary of the invention]
[0007] [Technical issues]
[0008] The present invention provides a composition for preparing a super absorbent polymer, the composition comprising clay, wherein the clay is uniformly dispersed and has excellent dispersion stability even when stored for a long period of time.
[0009] The present invention also provides a method for preparing a super absorbent polymer using the composition for preparing a super absorbent polymer.
[0010] [Technical solution]
[0011] According to one embodiment of the present invention, there is provided a composition for preparing a superabsorbent polymer, comprising: clay; a polymer dispersant comprising two or more functional groups selected from an amine group, a carbonyl group and a hydroxyl group; a water-soluble ethylenically unsaturated monomer having an acid group and at least a portion of the acid group being neutralized; and a polymerization initiator, wherein the content of the polymer dispersant is greater than 20 parts by weight to 200 parts by weight or less relative to 100 parts by weight of the clay.
[0012] According to another embodiment of the present invention, there is provided a method for preparing a super absorbent polymer, the method comprising the steps of: preparing an aqueous gel polymer by polymerizing the composition for preparing a super absorbent polymer by heating and / or irradiating light; preparing a base polymer by drying and pulverizing the aqueous gel polymer; and forming a surface crosslinked layer by further crosslinking the surface of the base polymer in the presence of a surface crosslinking agent.
[0013] According to another embodiment of the present invention, a superabsorbent polymer is provided, which includes: a cross-linked polymer of a water-soluble ethylenically unsaturated monomer, the water-soluble ethylenically unsaturated monomer having an acid group and at least a portion of the acid group being neutralized; and clay whose surface is modified with a polymer dispersant, the polymer dispersant including two or more functional groups selected from the group consisting of an amine group, a carbonyl group and a hydroxyl group, wherein the polymer dispersant is included in an amount of greater than 20 parts by weight to less than 200 parts by weight based on 100 parts by weight of the clay.
[0014] [Effects of the invention]
[0015] The composition for preparing a super absorbent polymer of the present invention contains clay and has a low sedimentation rate of clay particles and excellent dispersion stability even during long-term storage. Therefore, the composition for preparing a super absorbent polymer can be effectively used to prepare a super absorbent polymer having excellent absorption properties such as centrifugal retention capacity and pressurized absorption rate, etc. and improved gel strength. In addition, the super absorbent polymer prepared using the composition for preparing a super absorbent polymer has no concerns about discoloration and exhibits excellent color characteristics. [Drawings]
[0016] Figure 1 The photographs showing the compositions for preparing super absorbent polymers of Examples 1-1 to 1-3 (each labeled as Examples 1 to 3), Comparative Examples 1-3 and Comparative Examples 1-4 (each labeled as Comparative Examples 3 and 4) were taken 48 hours after preparing the compositions. [Specific implementation method]
[0017] The terms used in this specification are only used to explain exemplary embodiments and are not intended to limit the present invention. Singular expressions may include plural expressions unless there is a different expression in the context. It must be understood that the terms "including", "equipped" or "having" in this specification are only used to specify the existence of features, steps, components or combinations thereof of the effects taken, and do not exclude the existence or possibility of adding one or more different features, steps, components or combinations thereof in advance.
[0018] The present invention can be modified in various ways and has various forms, and specific exemplary embodiments are illustrated and explained in detail in the following description. However, this does not mean that the present invention is limited to specific exemplary embodiments, and it must be understood that the present invention includes all modifications, equivalents or replacements included in the spirit and technical scope of the present invention.
[0019] As used herein, "clay" refers to particles of a phyllosilicate mineral, or an aggregate of a plurality of such particles, and "clay dispersion" refers to a dispersion in which clay is dispersed in a solvent.
[0020] As used herein, (meth)acrylate is used as a meaning including both acrylate and methacrylate.
[0021] As used herein, "base polymer" or "base polymer powder" refers to a polymer that is not surface-modified or surface-crosslinked, and is in the form of particles or powder prepared by drying or pulverizing a polymer obtained by polymerizing a water-soluble ethylenically unsaturated monomer.
[0022] Hereinafter, the present invention will be described in detail.
[0023] According to one embodiment of the present invention, there is provided a composition for preparing a superabsorbent polymer, comprising: clay; a polymer dispersant comprising two or more functional groups selected from an amine group, a carbonyl group and a hydroxyl group; a water-soluble ethylenically unsaturated monomer having an acid group and at least a portion of the acid group being neutralized; and a polymerization initiator, wherein the content of the polymer dispersant is greater than 20 parts by weight to 200 parts by weight or less relative to 100 parts by weight of the clay.
[0024] Since the polymer dispersant contains two or more functional groups selected from the group consisting of amine, carbonyl and hydroxyl groups, the composition for preparing super absorbent polymers can significantly improve the dispersion stability of clay. Clay has a layered structure in which layers of silicate platelets about 1 nm thick are stacked on each other due to strong van der Waals attraction. The polymer dispersant binds to the surface of the clay and delaminates the silicate layers (i.e., disperses them so that the interlayer distance exceeds 1 nm). Since chemically delaminated clays exhibit significantly improved dispersion stability, even when the clay dispersion is included in a composition for preparing a super absorbent polymer comprising an alkali metal salt or a basic compound, the clay particles can be uniformly dispersed in the composition without agglomeration or sedimentation.
[0025] Therefore, the super absorbent polymer prepared using the composition for preparing super absorbent polymer can have further improved absorption properties, such as centrifugal retention capacity, pressurized absorption rate, etc. In addition, since the polymer dispersant does not cause discoloration of the super absorbent polymer, the composition for preparing super absorbent polymer of the present invention can produce high-quality super absorbent polymer with excellent absorption performance and color characteristics.
[0026] As the clay, swelling or non-swelling clay can be used. Swelling clay is a layered organic material having water absorption, and montmorillonite, saponite, nontronite, laponite, beidellite, hectorite, vermiculite, magadiite, bentonite, etc. can be used. As the non-swelling clay, kaolin, serpentine, mica, etc. can be used. Clay can be used alone or as a mixture of two or more thereof.
[0027] Clay having an average particle size (D50) of 0.025 μm or more, or 0.05 μm or more, or 0.1 μm or more, or 1 μm or more, and 10 μm or less, or 8 μm or less, or 5 μm or less can be used. When the average particle size (D50) of the clay is less than 0.025 μm, the effect of improving the gel strength of the superabsorbent polymer may not be fully obtained. When the average particle size (D50) of the clay is greater than 10 μm, it is difficult to achieve uniform dispersion in the water system due to the strong interlayer attraction of the clay, and it is difficult to uniformly modify the surface of the clay, so there may be a problem of not ensuring transparency after dispersion. The average particle size of the clay can be measured by laser diffraction and dynamic light scattering methods using a particle size analyzer.
[0028] Here, "particle size Dn" refers to the particle size at the n% point of the cumulative distribution of the number of particles according to the particle size, and D50 refers to the particle size at the 50% point of the cumulative distribution of the number of particles according to the particle size. The average particle size (D50) of the clay can be measured by laser diffraction and dynamic light scattering methods using a particle size analyzer. Specifically, the powder to be measured is dispersed in a dispersion medium and introduced into a commercially available laser diffraction particle size measuring device (e.g., Mastersizer 3000 from Malvern) to produce a particle size distribution based on the difference in the diffraction pattern when the particles pass through the laser beam. D50 can be measured by calculating the particle diameter at the point where 50% of the cumulative distribution of the particle count that reaches the particle diameter in the measuring device.
[0029] The polymer dispersant includes two or more functional groups selected from the group consisting of an amine group, a carbonyl group, and a hydroxyl group, and is used in an amount of greater than 20 parts by weight to less than or equal to 200 parts by weight relative to 100 parts by weight of the clay.
[0030] As used herein, "two or more functional groups selected from the group consisting of an amine group, a carbonyl group, and a hydroxyl group" is used as the meaning of two or more functional groups including an amine group, a carbonyl group, and a hydroxyl group in combination, such as an amide group including both an amine group and a carbonyl group, a carboxyl group including both a carbonyl group and a hydroxyl group, etc. A "polymer dispersant including an amine group and a carbonyl group" may include an amine group and a carbonyl group in the molecule, respectively, or may include an amide group in combination with an amine group and a carbonyl group.
[0031] The polymer dispersant containing the functional group can be bound to the clay surface due to the unshared electrons of the nitrogen and oxygen atoms, and can induce charges in the polymer due to the resonance phenomenon in the composition for preparing the superabsorbent polymer having a high ion concentration. Due to these properties, the polymer dispersant can improve the dispersibility of the clay by delaminating the layered structure of the clay. In addition, the polymer dispersant does not cause discoloration of the superabsorbent polymer or deteriorate its physical properties, and therefore, can be suitably used in the preparation of the superabsorbent polymer.
[0032] From this point of view, the polymer dispersant may preferably include an amine group and a carbonyl group; or a carbonyl group and a hydroxyl group. More preferably, the polymer dispersant may include an amide group and / or a carboxyl group.
[0033] Specific examples of the polymer dispersant may include one or more selected from the group consisting of polyvinyl pyrrolidone, polyacrylamide, and polyacrylic acid. Preferably, polyvinyl pyrrolidone may be used as the polymer dispersant.
[0034] The molecular weight of the polymer dispersant is not particularly limited. However, for example, a polymer dispersant having a weight average molecular weight of 2,500 g / mol or more, or 5,000 g / mol or more, or 10,000 g / mol or more, and 200,000 g / mol or less, or 100,000 g / mol or less, or 40,000 g / mol or less can be used. When the weight average molecular weight of the polymer dispersant is less than 2,500 g / mol, there may be problems in ensuring dispersibility and long-term stability because it is difficult to ensure sufficient distance between the silicate layers of the clay when the polymer dispersant is bonded to the clay surface. When the weight average molecular weight is greater than 200,000 g / mol, the method is difficult and ineffective for surface modification of the clay, so it is preferred to meet the above range.
[0035] The weight average molecular weight of the polymeric dispersant can be determined by gel permeation chromatography (GPC) using polystyrene standards.
[0036] For example, GPC analysis can be performed on a Waters PL-GPC220 instrument using a Polymer Laboratories PLgelMIX-B 300 mm long column under the following conditions:
[0037] Column temperature: 160°C
[0038] Solvent: 1,2,4-Trichlorobenzene
[0039] Flow rate: 1mL / min
[0040] Sample: Mix to a concentration of 10 mg / 10 mL and then provide in a volume of 200 μL
[0041] The Mw and Mn values were obtained using a calibration curve formed with polystyrene standards (nine types of polystyrene standards having molecular weights of 2,000 / 10,000 / 30,000 / 70,000 / 200,000 / 700,000 / 2,000,000 / 4,000,000 / 10,000,000).
[0042] In order to ensure the dispersibility of the clay, the polymer dispersant is used in an amount of greater than 20 parts by weight to less than or equal to 200 parts by weight, preferably 23 parts by weight or more, or 25 parts by weight or more, and 150 parts by weight or less, or 100 parts by weight or less, relative to 100 parts by weight of the clay.
[0043] When the content of the polymer dispersant is less than 20 parts by weight relative to 100 parts by weight of the clay, the surface modification degree of the clay is insufficient, and thus the interlayer spacing of the clay may not be sufficiently widened. Therefore, the dispersion stability of the clay is insufficient, and thus the clay particles may be easily agglomerated. In addition, when the content of the polymer dispersant is too high by exceeding 200 parts by weight relative to 100 parts by weight of the clay, the polymer dispersant reduces the effect of improving physical properties that can be provided by the clay, resulting in deterioration of the physical properties of the superabsorbent polymer.
[0044] The content of clay in the composition for preparing superabsorbent polymer may be 0.1 parts by weight or more, or 0.2 parts by weight or more, or 0.25 parts by weight or more, and 1 part by weight or less, or 0.7 parts by weight or less, or 0.5 parts by weight or less, based on 100 parts by weight of ethylenically unsaturated monomers.
[0045] The water-soluble ethylenically unsaturated monomer has an acid group, and at least a portion of the acid group may be neutralized. The water-soluble ethylenically unsaturated monomer is partially neutralized with an alkaline substance such as an alkali metal salt or an alkaline compound. As the alkali metal salt capable of neutralizing the water-soluble ethylenically unsaturated monomer, sodium acrylate and the like may be cited, or as the alkaline compound, caustic soda (NaOH), potassium hydroxide, ammonium hydroxide and the like may be used.
[0046] The neutralization degree of the water-soluble ethylenically unsaturated monomer is 50% to 95%, preferably 70% to 85%. When the neutralization degree of the monomer is low, the water absorbency of the superabsorbent polymer to be prepared may be reduced, and when the neutralization degree is high, the monomer may precipitate and it may be difficult to prepare the superabsorbent polymer.
[0047] As the water-soluble ethylenically unsaturated monomer, any monomer can be used without particular limitation as long as it is generally used for preparing superabsorbent polymers. Preferably, any one or more selected from anionic monomers and salts thereof, nonionic hydrophilic monomers and amino-containing unsaturated monomers and quaternary compounds thereof can be used. Specific examples of water-soluble ethylenically unsaturated monomers may include one or more selected from: anionic monomers such as acrylic acid, methacrylic acid, maleic anhydride, fumaric acid, crotonic acid, itaconic acid, 2-acryloylethanesulfonic acid, 2-methacryloylethanesulfonic acid, 2-(meth)acryloylpropanesulfonic acid or 2-(meth)acrylamide-2-methylpropanesulfonic acid and salts thereof; nonionic hydrophilic monomers such as (meth)acrylamide, N-substituted (meth)acrylates, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, methoxypolyethylene glycol (meth)acrylate or polyethylene glycol (meth)acrylate; and amino group-containing unsaturated monomers such as (N,N)-dimethylaminoethyl (meth)acrylate or (N,N)-dimethylaminopropyl (meth)acrylamide, and quaternary compounds thereof.
[0048] The concentration of the water-soluble ethylenically unsaturated monomer may be about 20 to 60 parts by weight, preferably 40 to 60 parts by weight, relative to 100 parts by weight of the composition for preparing the super absorbent polymer, and may be an appropriate concentration in consideration of the polymerization time and reaction conditions, etc. When the monomer concentration is too low, the yield of the super absorbent polymer may be low, and problems may arise in terms of economic feasibility. When the concentration is too high, part of the monomer may precipitate, or problems may arise during processing, such as low pulverization efficiency when the polymerized hydrogel polymer is pulverized, and the physical properties of the super absorbent polymer may deteriorate.
[0049] As the polymerization initiator, depending on the polymerization method, photopolymerization may use a photopolymerization initiator, and thermal polymerization may use a thermal polymerization initiator.
[0050] However, even if photopolymerization is performed, a certain amount of heat may be generated by UV irradiation or the like, and may also be generated by a polymerization reaction which is an exothermic reaction. Therefore, a thermal polymerization initiator may be further used.
[0051] The thermal polymerization initiator is not particularly limited, but one or more selected from persulfate-based initiators, azo-based initiators, hydrogen peroxide and ascorbic acid can be preferably used. Specifically, examples of persulfate-based initiators can include sodium persulfate (Na2S2O8), potassium persulfate (K2S2O8), ammonium persulfate ((NH4)2S2O8), etc. Examples of azo-based initiators can include 2,2-azobis(2-amidinopropane) dihydrochloride, 2,2-azobis-(N,N-dimethylene)isobutyramidine dihydrochloride, 2-(carbamoyl azo)isobutyronitrile, 2,2-azobis[2-(2-imidazoline-2-yl)propane] dihydrochloride or 4,4-azobis-(4-cyanovaleric acid), etc.
[0052] The photopolymerization initiator is not particularly limited, but one or more selected from benzoin ether, dialkyl acetophenone, hydroxyalkyl ketone, glyoxylic acid phenyl ester, benzyl dimethyl ketal, acyl phosphine and α-amino ketone can be preferably used. Meanwhile, a specific example of the acyl phosphine can include diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide.
[0053] The composition for preparing superabsorbent polymer may include solvent. Applicable solvent can be used without restriction in its composition, as long as it can dissolve the above components. For example, one or more selected from water, ethanol, ethylene glycol, diethylene glycol, triethylene glycol, 1,4-butylene glycol, propylene glycol, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, methyl ethyl ketone, acetone, methyl amyl ketone, cyclohexanone, cyclopentanone, diethylene glycol monomethyl ether, diethylene glycol ethyl ether, toluene, xylene, butyrolactone, carbitol, methyl cellosolve acetate and N,N-dimethylacetamide can be used as solvent.
[0054] Meanwhile, the composition for preparing the superabsorbent polymer may further include a crosslinking agent. As the crosslinking agent, a crosslinking agent having one or more functional groups capable of reacting with the water-soluble substituent of the water-soluble ethylenically unsaturated monomer and one or more ethylenically unsaturated groups may be used; or a crosslinking agent having two or more functional groups capable of reacting with the water-soluble substituent of the monomer and / or the water-soluble substituent formed by the hydrolysis of the monomer may be used.
[0055] Specific examples of the cross-linking agent may include one or more selected from N,N'-methylenebisacrylamide, trimethylolpropane tri(meth)acrylate, ethylene glycol di(meth)acrylate, (meth)acrylate, propylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol (meth)acrylate, butanediol di(meth)acrylate, butanediol di(meth)acrylate, diethylene glycol di(meth)acrylate, hexanediol di(meth)acrylate, triethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, dipentaerythritol pentaacrylate, glycerol tri(meth)acrylate, pentaerythritol tetraacrylate, triallylamine, ethylene glycol diglycidyl ether, propylene glycol, glycerol and ethylene carbonate.
[0056] The content of the crosslinking agent is 0.01 parts by weight or more, 0.05 parts by weight or more, 0.1 parts by weight or more, or 0.3 parts by weight or more, and 2 parts by weight or less, 1.5 parts by weight or less, or 1 part by weight or less, relative to 100 parts by weight of the water-soluble ethylenically unsaturated monomer, thereby crosslinking the polymerized polymer.
[0057] The composition for preparing the super absorbent polymer may further include additives such as a foaming agent, a thickener, a plasticizer, a preservative stabilizer, an antioxidant, and the like as required.
[0058] For example, the composition for preparing the superabsorbent polymer may contain one or more foaming agents selected from the group consisting of sodium bicarbonate, sodium carbonate, potassium bicarbonate, potassium carbonate, calcium bicarbonate, calcium carbonate, magnesium bicarbonate and magnesium carbonate as the foaming agent.
[0059] The amount of the foaming agent added may be 0.01 parts by weight or more, or 0.05 parts by weight or more, or 0.08 parts by weight or more, and 0.5 parts by weight or less, 0.3 parts by weight or less, or 0.2 parts by weight or less relative to 100 parts by weight of the monomer.
[0060] The preparation method of the composition for preparing super absorbent polymer is not particularly limited. For example, the composition for preparing super absorbent polymer can be prepared by mixing the following components at one time: clay; polymer dispersant; water-soluble ethylenically unsaturated monomer; alkali metal salt or basic compound capable of neutralizing the water-soluble ethylenically unsaturated monomer; and polymerization initiator in the presence of a solvent.
[0061] Alternatively, the composition for preparing a super absorbent polymer can be prepared by mixing clay and a polymer dispersant with a solvent (the solvent in the composition for preparing a super absorbent polymer can be used) to prepare a clay dispersion, and then mixing the clay dispersion with a water-soluble ethylenically unsaturated monomer; an alkali metal salt or a basic compound capable of neutralizing the water-soluble ethylenically unsaturated monomer; and a polymerization initiator.
[0062] By including clay and a polymer dispersant, the composition for preparing a super absorbent polymer maintains excellent dispersion stability in the composition without clay particles agglomerating or precipitating with each other.
[0063] Specifically, the sedimentation rate of the clay in the composition for preparing the superabsorbent polymer may be 100 μm / s or less, preferably 50 μm / s or less, or 30 μm / s or less, or 10 μm / s or less, and 1 μm / s or more, or 5 μm / s or more. The method for measuring the sedimentation rate will be described in detail in the following experimental examples.
[0064] A composition for preparing a super absorbent polymer comprises clay, wherein the clay maintains excellent dispersion stability due to a polymer dispersant comprising two or more functional groups selected from the group consisting of an amine group, a carbonyl group and a hydroxyl group, and thus the composition can be suitably used for preparing a super absorbent polymer having excellent absorption performance without worrying about discoloration.
[0065] Therefore, according to another embodiment of the present invention, a super absorbent polymer and a method of preparing the same using the composition for preparing the super absorbent polymer are provided.
[0066] The super absorbent polymer comprises a cross-linked polymer of a water-soluble ethylenically unsaturated monomer having an acidic group, at least a portion of which is neutralized; and clay having a surface modified with a polymer dispersant, the polymer dispersant comprising two or more functional groups selected from an amine group, a carbonyl group, and a hydroxyl group. The super absorbent polymer may comprise the polymer dispersant in an amount of greater than 20 parts by weight to less than 200 parts by weight based on 100 parts by weight of the clay.
[0067] The super absorbent polymer prepared from the above-mentioned monomer composition for preparing a super absorbent polymer has a form in which the clay is uniformly dispersed inside and outside the cross-linked polymer.
[0068] The method for preparing a super absorbent polymer comprises the following steps: preparing a hydrous gel polymer by performing a polymerization reaction of a composition for preparing a super absorbent polymer by heating and / or irradiating light; preparing a base polymer by drying and pulverizing the hydrous gel polymer; and forming a surface crosslinked layer by further crosslinking the surface of the base polymer in the presence of a surface crosslinking agent.
[0069] According to the polymerization energy source, the polymerization method is mainly divided into thermal polymerization and photopolymerization. When thermal polymerization is performed, it can be generally performed in a reactor such as a kneader equipped with a stirring shaft. When photopolymerization is performed, it can be performed in a reactor equipped with a movable conveyor belt. The above-mentioned polymerization method is only an example, and the present invention is not limited to the above-mentioned polymerization method.
[0070] For example, the hydrogel polymer obtained by performing thermal polymerization while supplying hot air to the above-mentioned reactor such as a kneader equipped with a stirring shaft or heating the reactor may have a size of centimeters or millimeters when it is discharged from the outlet of the reactor, depending on the type of stirring shaft equipped in the reactor. Specifically, the size of the obtained hydrogel polymer may vary depending on the concentration of the monomer composition fed thereto or the feeding rate, etc., and a hydrogel polymer having a weight average particle diameter of about 2 mm to about 50 mm may be generally obtained.
[0071] In addition, as mentioned above, when photopolymerization is carried out in a reactor equipped with a movable conveyor, the obtained hydrogel polymer can generally be a sheet-like hydrogel polymer with a band width. In this case, the thickness of the polymer sheet can change according to the concentration and feed rate of the monomer composition fed thereto. Usually, it is preferred to provide a monomer composition so that a sheet-like polymer having a thickness of about 0.5 cm to about 5 cm can be obtained. When the monomer composition is supplied to such an extent that the thickness of the sheet-like polymer becomes too thin, it is undesirable because the production efficiency is low, and when the thickness of the sheet-like polymer is greater than 5 cm, due to the excessive thickness, polymerization may not occur uniformly over the entire thickness.
[0072] The hydrogel polymer obtained by the above method may have a water content of about 40% by weight to about 80% by weight. Meanwhile, the "water content" used herein refers to the weight occupied by water relative to the total weight of the hydrogel polymer, which may be a value obtained by subtracting the weight of the dried polymer from the weight of the hydrogel polymer. Specifically, the water content may be defined as a value calculated by measuring the weight loss caused by evaporation of water in the polymer during a drying process in which the temperature of the polymer is increased by infrared heating. At this time, the water content is measured under the drying conditions determined as follows: the drying temperature is increased from room temperature to about 180°C, and then the temperature is maintained at 180°C, and the total drying time is set to 20 minutes, including 5 minutes for the temperature increase step.
[0073] After cross-linking and polymerizing the monomers, the base polymer powder can be obtained by drying, pulverizing, and classifying. It is suitable to prepare and provide the base polymer powder and the super absorbent polymer obtained therefrom each having a particle size of 150 μm to 850 μm through such pulverizing and classifying processes. More specifically, at least about 95% by weight or more of the base polymer powder and the super absorbent polymer obtained therefrom may have a particle size of about 150 μm to about 850 μm, and fine particles having a particle size of less than 150 μm may be less than about 3% by weight.
[0074] As described above, when the particle size distributions of the base polymer powder and the super absorbent polymer are adjusted to a desired range, the finally prepared super absorbent polymer can exhibit the above-mentioned physical properties and excellent liquid permeability.
[0075] On the other hand, the methods of performing drying, pulverizing and classification will be described in more detail as follows.
[0076] First, regarding the drying of the hydrogel polymer, a coarse pulverization step may be further performed before drying, if necessary, in order to improve the efficiency of the drying step.
[0077] In this regard, the pulverizer used herein is not limited to its configuration, and specifically, it may include any one selected from the group consisting of a vertical pulverizer, a turbine cutter, a turbine grinder, a rotary shredder, a shredder, a disc pulverizer, a shredder, a crusher, a shredder and a disc cutter, but is not limited to the above examples.
[0078] In this regard, a coarse pulverization step may be performed such that the particle size of the hydrogel polymer becomes about 2 mm to about 10 mm.
[0079] Due to the high water content of the hydrogel polymer, it is technically not easy to pulverize into a particle size of less than 2 mm, and agglomeration may occur between the pulverized particles. At the same time, when the polymer is pulverized into a particle size greater than 10 mm, the effect of improving efficiency in the subsequent drying step may not be significant.
[0080] The hydrogel polymer coarsely pulverized as described above is dried or the hydrogel polymer without coarse pulverization step after polymerization is dried immediately. In this regard, the drying temperature of the drying step may be about 150° C. to about 250° C. When the drying temperature is lower than 150° C., it is considered that the drying time becomes too long and the physical properties of the finally formed superabsorbent polymer may be deteriorated. When the drying temperature is higher than 250° C., it is considered that only the polymer surface is excessively dried, and thus fine particles may be generated in the subsequent pulverization process, and the physical properties of the finally formed superabsorbent polymer may be deteriorated. Therefore, the drying may be preferably performed at a temperature of about 150° C. to about 200° C., more preferably at a temperature of about 160° C. to about 180° C.
[0081] Meanwhile, considering process efficiency, the drying step may be performed for about 20 minutes to about 90 minutes, but is not limited thereto.
[0082] In the drying step, any drying method may be selected and used without limitation in consideration of the composition, as long as it is generally used in a method for drying a hydrogel polymer. Specifically, the drying step may be performed by a method such as hot air supply, infrared irradiation, microwave irradiation or ultraviolet irradiation. When the above drying step is completed, the water content of the polymer may be about 0.1 wt % to about 10 wt %.
[0083] Next, a step of pulverizing the dried polymer obtained in the drying step is performed.
[0084] The polymer powder obtained by the pulverization step may have a particle size of about 150 μm to about 850 μm. Specific examples of pulverizers that can be used to achieve the above particle size may include a pin mill, a hammer mill, a screw mill, a roller mill, a disc mill or a vibration mill, etc., but are not limited to the above examples.
[0085] In order to manage the physical properties of the superabsorbent polymer powder finally commercialized after the pulverization step, a separate process of classifying the polymer powder obtained after pulverization according to the particle size may be performed. Preferably, polymers having a particle size of about 150 μm to about 850 μm are classified, and only polymer powders having such a particle size are subjected to a surface crosslinking reaction and then commercialized.
[0086] Meanwhile, after performing the process of forming the above-mentioned base polymer powder, a surface crosslinked layer may be formed by additionally crosslinking the surface of the base polymer powder in the presence of a surface crosslinking agent, and as a result, a super absorbent polymer may be prepared.
[0087] As the surface crosslinking agent, a compound capable of reacting with a functional group of a polymer is used, for example, a polyol compound, a polyepoxy compound, a polyamine compound, a halogenated epoxy compound, a condensate of a halogenated epoxy compound, an oxazoline compound or an alkylene carbonate compound can be used.
[0088] Specifically, examples of the polyol compound may include one or more selected from di-, tri-, tetra- or polyethylene glycol, 1,3-propylene glycol, dipropylene glycol, 2,3,4-trimethyl-1,3-pentanediol, polypropylene glycol, glycerol, polyglycerol, 2-butene-1,4-diol, 1,4-butanediol, 1,3-butanediol, 1,5-pentanediol, 1,6-hexanediol and 1,2-cyclohexanedimethanol.
[0089] In addition, as the polyepoxide, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether and glycidol can be used. As the polyamine compound, one or more selected from ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, polyethyleneimine and polyamide polyamine can be used.
[0090] As the halogenated epoxy compound, epichlorohydrin, epibromohydrin, and α-methylepichlorohydrin may be used. Meanwhile, examples of the mono-, di- or polyoxazolidinone compound may include 2-oxazolidinone and the like.
[0091] As the alkylene carbonate compound, ethylene carbonate or the like can be used.
[0092] These compounds may be used alone or in combination.
[0093] The content of the surface crosslinking agent to be added may be appropriately specifically selected depending on the type of the surface crosslinking agent added or the reaction conditions, but the surface crosslinking agent may generally be used in an amount of 0.001 to 5 parts by weight, preferably 0.01 to 2 parts by weight, and more preferably 0.05 to 3 parts by weight, relative to 100 parts by weight of the base polymer.
[0094] In addition, the method of adding the surface crosslinking agent to the base polymer powder is not limited in configuration. For example, a method of placing the surface crosslinking agent and the base polymer powder in a reactor and mixing them, a method of spraying the surface crosslinking agent onto the base polymer powder, a method of continuously supplying the base polymer powder and the surface crosslinking agent to a continuously operated mixer and mixing them, etc. can be used.
[0095] When adding a surface crosslinking agent, water and methanol may be further added after mixing. When adding water and methanol, it is advantageous that the surface crosslinking agent can be uniformly dispersed in the base polymer powder. At this time, the amount of water and methanol to be added may preferably be controlled relative to 100 parts by weight of the base polymer powder to induce uniform dispersion of the surface crosslinking agent, prevent agglomeration of the base polymer powder, and simultaneously optimize the surface penetration depth of the surface crosslinking agent.
[0096] The surface crosslinking reaction can be carried out by heating the base polymer powder to which the surface crosslinking agent is added at a temperature of about 160°C or more for about 20 minutes or more. Specifically, in order to prepare a superabsorbent polymer that more appropriately meets the physical properties according to one embodiment, the surface crosslinking process conditions include a maximum reaction temperature of about 180°C to 200°C, and a holding time of about 20 minutes or more, or about 20 minutes or more and 1 hour or less at the maximum reaction temperature. In addition, the heating time taken from the temperature at the time of the initial reaction (e.g., about 160°C or more, or about 160°C to 170°C) to the maximum reaction temperature can be controlled to be about 10 minutes or more, or about 10 minutes or more and about 1 hour or less. It has been confirmed that a superabsorbent polymer that appropriately meets the physical properties of one embodiment can be prepared by satisfying the above-mentioned surface crosslinking process conditions.
[0097] The method for increasing the surface crosslinking reaction temperature is not particularly limited. Heating can be carried out by providing a heating medium or directly providing a heat source. In this regard, the type of applicable heating medium can be steam, hot air, hot fluids such as hot oil, but the present invention is not limited thereto. The temperature of the heating medium to be provided can be appropriately selected by considering the mode of the heating medium, the heating rate and the target temperature. At the same time, as the heat source directly provided, an electric heater or a gas heater can be used, but the present invention is not limited to these examples.
[0098] The superabsorbent polymer obtained according to the above preparation method can show very excellent performance, wherein the overall physical properties such as water retention capacity and pressure absorption rate are improved at the same time, and therefore, it can be suitable for sanitary products such as diapers.
[0099] Hereinafter, preferred exemplary embodiments are provided to better understand the present invention. However, the following exemplary embodiments are only used to illustrate the present invention, and it is obvious to those skilled in the art that various changes and modifications may be made without departing from the scope and spirit of the present invention as disclosed in the appended claims.
[0100] [Example]
[0101] <Preparation of Composition for Preparing Superabsorbent Polymer>
[0102] Example 1-1
[0103] 450 g of acrylic acid, 3 g of polyethylene glycol diacrylate 400, and 0.04 g of diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide were mixed, and 580 g of a 31.5% sodium hydroxide aqueous solution was introduced to prepare an acrylic monomer composition.
[0104] Separately, 5 g of ZrO2 beads as a pulverizing medium were weighed and placed in a 10 mL vial. 12 mg of polyvinyl pyrrolidone (PVP, Aldrich's PVP10; weight average molecular weight 10000 g / mol) was added thereto as a dispersant; then 24 mg of clay powder (bentonite, BYK's OPTIGELCK, particle size range 1-5 μm, average particle size (D50) 3 μm) was added. 4.7 g of acrylic monomer composition was added thereto, and a composition for preparing a superabsorbent polymer was prepared by oscillating and mixing at 300 rpm using an oscillator (JEIOTECH, SK-600) for 4 hours.
[0105] Examples 1-2 to 1-3 and Comparative Examples 1-1 to 1-4
[0106] The compositions for preparing super absorbent polymers of Examples 1-2 to 1-3 and Comparative Examples 1-1 to 1-4 were respectively prepared in the same manner as in Example 1-1, except that the type of the dispersant and the input amount thereof were changed as shown in Table 1 below.
[0107] The poly(acrylic acid) of Examples 1-5 was a product having a weight average molecular weight of 25,000 g / mol manufactured by Wako Pure Chemical, and the poly(ethylene oxide) of Comparative Examples 1-6 was a product having a weight average molecular weight of 100,000 g / mol manufactured by Sigma-Aldrich.
[0108] DISPERBYK-102 (BYK) used in Comparative Examples 1-2 is a phosphate-based polymer, and Sokalan HP-20 (BASF) used in Comparative Examples 1-3 is a polyethyleneimine-based polymer dispersant.
[0109] [Table 1]
[0110]
[0111] Experimental Example 1: Evaluation of physical properties of compositions for preparing superabsorbent polymers
[0112] The physical properties of the compositions for preparing the super absorbent polymers of Examples 1-1 to 1-5 and Comparative Examples 1-1 to 1-6 were evaluated by the following methods, respectively, and the results are shown in Table 2.
[0113] (1) Deposition rate
[0114] The sedimentation rate of the clay particles of each composition of Examples 1-1 to 1-3 and Comparative Examples 1-1 to 1-4 was measured using a LUMiSizer dispersion & particle size analyzer.
[0115] Specifically, 1.6 mL of the composition for preparing a super absorbent polymer was taken, placed in a 10 mm PC cell, and then mounted on a LUMiSizer to measure a transmittance curve of 400 points at intervals of 10 seconds at a temperature of 25° C., 1,500 rpm (~280 G). In the transmittance curve thus measured, the threshold was set to 21% and the sedimentation rate was calculated.
[0116] (2) Dispersion stability after 48 hours
[0117] 4 g of each of the compositions for preparing super absorbent polymers of Examples 1-1 to 1-3 and Comparative Examples 1-1 to 1-4 was placed in a 10 ml vial, the vial was placed in a vial stand, and left at a temperature of 25° C. for 48 hours. Next, the supernatant was visually observed to see if layer separation occurred. When layer separation occurred, it was evaluated as having no dispersion stability (X), and when layer separation did not occur, it was evaluated as having dispersion stability (O).
[0118] [Table 2]
[0119]
[0120] Referring to Table 2, in the compositions for preparing super absorbent polymers of Examples 1-1 to 1-3 in which a clay dispersion containing 25 to 50 parts by weight of a PVP dispersant relative to 100 parts by weight of clay was added, sedimentation of clay did not occur. It was confirmed that dispersion stability was excellent even after 48 hours.
[0121] <Preparation of Superabsorbent Polymer>
[0122] Example 2-1
[0123] (1) Preparation of 4 wt% clay dispersion
[0124] In a flask, 2 g of clay (bentonite, BYK's OPTIGELCK, particle size range 1-5 μm, average particle size 3 μm) and 1 g (50 parts by weight relative to 100 parts by weight of clay) of polyvinylpyrrolidone (Aldrich's PVP10; weight average molecular weight 10000) as a polymer dispersant were added, and water was added so that the total weight of the mixture was 50 g. The mixture was stirred at 500 rpm for 12 hours with a magnetic stirrer to prepare a 4 wt% clay dispersion.
[0125] (2) Preparation of superabsorbent polymer
[0126] In a 3 L glass container, 450 g of acrylic acid (AA), 3 g of polyethylene glycol diacrylate 400 (PEGDA400), and 0.04 g of diphenyl (2,4,6-tribenzoyl) -phosphine oxide were placed and dissolved, and then 580 g of a 31.5% sodium hydroxide aqueous solution was added to prepare an acrylic monomer composition.
[0127] 4 wt % of the clay dispersion prepared in (1) was added to the monomer composition so that the content of the clay was 0.5 wt % relative to 100 wt % of acrylic acid, and sodium bicarbonate (SBC) was added as a carbonate-based foaming agent in an amount of 0.1 wt % relative to 100 wt % of acrylic acid, thereby preparing a composition for preparing a superabsorbent polymer.
[0128] 1000 g of the composition for preparing a superabsorbent polymer was poured into a stainless steel container having a width of 250 mm, a length of 250 mm and a height of 30 mm, and the container was irradiated with ultraviolet rays (irradiation dose of 10 mV / cm 2 ) was subjected to UV polymerization for 90 seconds to obtain an aqueous gel polymer.
[0129] Thereafter, the thus obtained sheet-like hydrogel polymer was put into a meat grinder to obtain a hydrogel particle powder, which was then dried in an oven, and as a result, the water content of the dried product was 1% or less. The dried particles were pulverized with a pulverizer and classified to prepare a base polymer having a size of 150 μm to 850 μm.
[0130] To 100 g of the base polymer powder, 6 g of an aqueous solution of a surface crosslinking agent containing 3 g of ethylene carbonate was sprayed and stirred at room temperature to uniformly distribute the surface crosslinking solution on the base polymer powder. Then, the base polymer powder mixed with the surface crosslinking solution was placed in a surface crosslinking reactor, heated to 190° C. for 30 minutes, and subjected to a surface crosslinking reaction at the same temperature for 15 minutes.
[0131] After the surface cross-linking process, the powder was classified using a standard mesh sieve of ASTM standard to prepare a super absorbent polymer having a particle size of 150 μm to 850 μm.
[0132] Examples 2-2 to 2-3 and Comparative Examples 2-1 to 2-3
[0133] Each clay dispersion was prepared in the same manner as in (1) of Example 2-1, except that when preparing the clay dispersion, the types and contents of clay and dispersant were adjusted as shown in the following Table 3. Then, superabsorbent polymers of Examples 2-2 to 2-3 and Comparative Examples 2-1 to 2-3 were prepared in the same manner as in (2) of Example 2-1.
[0134] [Table 3]
[0135]
[0136] Experimental Example 2: Evaluation of physical properties of superabsorbent polymers
[0137] The physical properties of the superabsorbent polymers of Examples 2-1 to 2-3 and Comparative Examples 2-1 to 2-3 were evaluated by the following methods, respectively, and the results are shown in Table 4.
[0138] (1) Effective absorptive capacity (EFFC)
[0139] The EFFC value was calculated according to the following equation.
[0140] EFFC=1 / 2(CRC+AUP)
[0141] In this equation, CRC and AUP are measured by the following method.
[0142] a) Measurement of Centrifuge Retention Capacity (CRC)
[0143] The CRC of superabsorbent polymers is measured according to EDANA method WSP 241.2.
[0144] In detail, from the polymer obtained by embodiment and comparative example, obtain the polymer of sieve classification with #30-50.This superabsorbent polymer W0(g) (about 0.2g) is evenly put into nonwoven bag, subsequently sealed, then immersed in physiological saline (0.9 wt %) at room temperature.After 30 minutes, use centrifuge under the condition of 250G, water is discharged from bag for 3 minutes, and the weight W2(g) of bag is measured.In addition, after not using polymer to carry out same procedure, measure weight W1(g) at this moment.
[0145] CRC (g / g) was calculated according to the following equation using the obtained weight.
[0146] CRC(g / g)={[W2(g)-W1(g)] / W0(g)}-1
[0147] b) Measurement of Absorption Under Pressure (AUP)
[0148] The AUP at 0.7 psi of superabsorbent polymers was measured according to EDANA method WSP 242.2.
[0149] First, when measuring the pressure absorption rate, the graded polymer used in the CRC measurement is used.
[0150] In detail, a 400-mesh stainless steel net is mounted on the bottom of a plastic cylinder having an inner diameter of 60 mm. Under the conditions of room temperature and 50% humidity, superabsorbent polymer W0 (g) (0.90 g) is uniformly dispersed on the stainless steel net. A piston capable of uniformly providing a load of 0.7 psi is placed thereon, wherein the outer diameter of the piston is slightly less than 60 mm, there is no gap between the inner wall of the cylinder and the piston, and the movement of the cylinder is not interrupted. At this time, the weight of the device is measured W4 (g).
[0151] After placing a glass filter having a diameter of 90 mm and a thickness of 5 mm in a petri dish having a diameter of 150 mm, a physiological saline solution composed of 0.9 wt% sodium chloride was poured until the surface level of the physiological saline solution became equal to the upper surface of the glass filter. A piece of filter paper having a diameter of 90 mm was placed on the glass filter. A measuring device was mounted on the filter paper so that the liquid was absorbed under load for 1 hour. After 1 hour, the weight W5 (g) was measured after the measuring device was lifted.
[0152] AUP (g / g) (g / g) was calculated from the obtained weight according to the following equation.
[0153] AUP(g / g)=[W5(g)-W4(g)] / W3(g)
[0154] (2) Color b
[0155] The color b value of the superabsorbent polymer is measured according to the ASTM D2985 standard.
[0156] [Table 4]
[0157] EFFC Color b Example 2-1 27.4 5.0 Example 2-2 27.4 5.3 Example 2-3 27.3 4.9 Comparative Example 2-1 26.8 4.8 Comparative Example 2-2 27.4 8.6 Comparative Example 2-3 27.0 11.3
[0158] Referring to Table 4, in Comparative Example 2-1, no dispersant was included, and thus the dispersion stability of the clay was reduced, resulting in a significant reduction in the EFFC value.
[0159] On the other hand, when comparing Examples 2-1 to 2-3 and Comparative Examples 2-2 and 2-3 each using a clay dispersion including a dispersant and clay, Comparative Examples 2-2 and 2-3 using Sokalan HP-20 as a dispersant were found to exhibit higher color b values than Examples 2-1 to 2-3 using PVP.
[0160] From the above results, it can be confirmed that the composition for preparing super absorbent polymer of the present invention has excellent dispersion stability of clay in the composition, thereby improving the absorption performance of the prepared super absorbent polymer. In addition, it can be confirmed that the super absorbent polymer prepared from the composition for preparing super absorbent polymer has no concerns about discoloration due to the dispersant and exhibits excellent color characteristics.
Claims
1. A composition for preparing a superabsorbent polymer, the composition comprising: clay; a polymer dispersant comprising two or more functional groups selected from the group consisting of an amine group, a carbonyl group, and a hydroxyl group; a water-soluble ethylenically unsaturated monomer having an acid group and at least a portion of the acid groups being neutralized; and Polymerization initiator, The content of the polymer dispersant is greater than 20 parts by weight and less than or equal to 200 parts by weight relative to 100 parts by weight of the clay. 2 . The composition for preparing a super absorbent polymer according to claim 1 , wherein the polymer dispersant is contained in an amount of 25 to 100 parts by weight relative to 100 parts by weight of the clay.
3. The composition for preparing a superabsorbent polymer according to claim 1 or 2, wherein the clay is one or more selected from the group consisting of montmorillonite, saponite, nontronite, laponite, beidellite, hectorite, vermiculite, magadiite, bentonite, kaolin, serpentine and mica. 4 . The composition for preparing a super absorbent polymer according to claim 1 , wherein the average particle size (D50) of the clay is 0.025 μm to 10 μm.
5. The composition for preparing a super absorbent polymer according to any one of claims 1 to 4, wherein the polymer dispersant comprises an amine group and a carbonyl group; or a carbonyl group and a hydroxyl group. 6 . The composition for preparing a super absorbent polymer according to claim 1 , wherein the polymer dispersant is one or more selected from the group consisting of polyvinylpyrrolidone, polyacrylamide and polyacrylic acid.
7. The composition for preparing a super absorbent polymer according to any one of claims 1 to 6, wherein the degree of neutralization of the water-soluble ethylenically unsaturated monomer is 50% to 95%. 8 . The composition for preparing a super absorbent polymer according to claim 1 , wherein the sedimentation rate of the clay is 100 μm / s or less.
9. A composition for preparing a superabsorbent polymer according to any one of claims 1 to 8, wherein the water-soluble ethylenically unsaturated monomer is one or more selected from the group consisting of anionic monomers such as acrylic acid, methacrylic acid, maleic anhydride, fumaric acid, crotonic acid, itaconic acid, 2-acryloylethane sulfonic acid, 2-methacryloylethane sulfonic acid, 2-(meth)acryloylpropane sulfonic acid or 2-(meth)acrylamide-2-methylpropane sulfonic acid, and salts thereof; Nonionic hydrophilic monomers, such as (meth)acrylamide, N-substituted (meth)acrylates, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, methoxypolyethylene glycol (meth)acrylate or polyethylene glycol (meth)acrylate; and Amino group-containing unsaturated monomers, such as (N,N)-dimethylaminoethyl (meth)acrylate or (N,N)-dimethylaminopropyl (meth)acrylamide, and quaternary compounds thereof.
10. The composition for preparing a super absorbent polymer according to any one of claims 1 to 9, wherein the content of the clay in the composition for preparing a super absorbent polymer is 0.1 to 1 parts by weight relative to 100 parts by weight of the ethylenically unsaturated monomer.
11. A method for preparing a superabsorbent polymer, the method comprising the steps of: Preparing a hydrogel polymer by polymerizing the composition for preparing a super absorbent polymer according to any one of claims 1 to 10 by heating and / or irradiating light; preparing a base polymer by drying and pulverizing the aqueous gel polymer; and The surface cross-linked layer is formed by further cross-linking the surface of the base polymer in the presence of a surface cross-linking agent.
12. A superabsorbent polymer comprising: a crosslinked polymer of a water-soluble ethylenically unsaturated monomer having an acid group and at least a portion of the acid groups being neutralized; and Clay whose surface is modified with a polymer dispersant, the polymer dispersant comprising two or more functional groups selected from the group consisting of an amine group, a carbonyl group and a hydroxyl group, The content of the polymer dispersant is greater than 20 parts by weight and less than 200 parts by weight relative to 100 parts by weight of the clay.
